Management of intangible resources at higher education institutions - Núñez Guerrero, Yilsy María (2015)
The organizations are developed in challenging and competitive environments, created by demands of societies, and marked by the global financial crisis that extends even to the Institutions of Higher Education (IHEs), which are aimed at meeting the needs of the environment and at strengthening the flow of information and collaboration with the society. In this context, an exploratory and descriptive investigation, which is considered as a first attempt to develop and empirically test the existing theoretical aspects of the subject arises. The objective is to determine the simultaneous influences exerted by intangible resources on strategic management in IHEs. These relationships were assessed by means of an analysis of covariance, which required the construction and validation of an appropriate system of measurement for each of the variables under study. Such analysis showed, as a result, that only two of the four hypotheses are significant, demonstrating that the intangible resources, namely Knowledge Management and Organizational Reputation, are those that directly affect strategic management processes, undertaken by the IHEs. From these findings, one has empirical references on the Management of Intangible Resources, thus highlighting the fact that the strategic management in IHEs can be substantially improved by means of the implementation of processes that involve the proper management of intangible assets that they have.